The gap between us: Perceptions of feminism and womanhood in Northern Ghana - evidence from Sagnarigu Municipal District - Tobias Tseer; Constance Awinpoka Akurugu; Robert Yakubu Ajuik (Cogent Arts & Humanities, 2023)
While earlier studies on gender equality in parts of Africa revealed some understanding of feminism and the gains made by feminists’ movements across African cities, these studies were conducted largely in urban areas where cultures have been immensely inflected by education, traditional and social media as well as cross-cultural norms and values. The extent to which feminism—a philosophical and a political movement committed to drawing attention to the conditions of differently situated women and empowering them to overcome oppression in its various forms—is understood in rural areas, including those in Northern Ghana, has received limited academic attention. Much scholarly work on this subject matter is predominated by privileged subjects, who on occasion are removed from the daily struggles and realities of women at the grassroots. This study deployed a grounded theoretical perspective, relying on in-depth interviews involving 30 women from diverse backgrounds and social classes to explore the knowledge and awareness of feminism, cultural conceptualisations of femininity and the resonance of such conceptualisations with contemporary feminists’ theorising. The study found that norms that frame women as men’s subordinates are deep-seated in the Sagnarigu Municipality, and indeed across much of northern Ghana. Furthermore, most women in the study area, an extremely heteropatriarchal setting, have very limited understanding of feminism. Feminism is considered as foreign and diametrically opposed to the cultural norms of the people.